Depiction of Caste System and Dalit Consciousness in Ratna BK’s Banda Ākāsh Khulepachhi (Cognition, 2024)
The article deals with the caste system and consciousness in relation to class consciousness and Dalit consciousness based on literary text. As Dalit literature portrays the socio-cultural, economic and political issues of Dalits, their inequal relation with the people, caste discrimination, exploitation and suppression and protest and movements; and, it also presents the potential avenues of resolution. The article explores the brutality of caste system and Dalit consciousness for rights, equality, justice, dignity and liberation of Dalits. For this purpose, some short stories from Ratna BK’s Banda Ākāsh Khulepachhi have been chosen for the interpretation. The stories reveal the ground reality of multiple layers discrimination and issues of Dalits, their protest and resolution. Furthermore, the research explores the socio-cultural and political awareness and protests of Dalits, and state’s pragmatic position to address the issues and agenda. The researcher employs the qualitative approach with exploratory and analytical methods. The Marxist concept of class consciousness connecting to Dalit consciousness is parallel applied as theoretical perspectives in this article.